A Lake Singkarak Resort Hotel. A Green Architecture Approach: Lake Singkarak Resort Hotel. A Green Architecture Approach - P Ananta, Bagas; Eddy, Firman; Abdillah, Wahyu (Talenta Publisher, 2022)
Lake Singkarak Resort Hotel is a building that provides lodging, eating and drinking facilities, sports, entertainment, and other facilities for a person or group who is on a tour to Lake Singkarak. The lake is located in Tanah Datar Regency in West Sumatra Province, Indonesia. The purpose of this study is to create a natural image and atmosphere at this resort hotel by using green architecture concept. The concept of Green Architecture Â is a design and development approach based on ecological principles and environmental conservation, which will produce a building that has environmental quality and creates a better and sustainable life. The use of this concept aims to follow the natural conditions in this area which are still naturally so that the building is in harmony with nature. Green architecture is an environmentally sound architecture and is based on concern for the conservation of the natural global environment with an emphasis on energy efficiency, sustainability patterns and a holistic approach.